Climate Modeling for Macroeconomic Policy : A Case Study for Pakistan - Burns, Andrew; Jooste, Charl; Schwerhoff, Gregor (World Bank, Washington, DC, 2021)
As the effects of climate change become increasingly evident, the design and implementation of climate-aware policies have assumed a more central role in the macroeconomic policy debate. With this has come an increasing recognition of the importance of introducing climate into the economic policy making tools used by central economic policy making agencies (such as ministries of finance and ministries of planning). This paper integrates climate outcomes into a macro-structural model for Pakistan, the kind of model that is suitable for use on a regular basis by ministry staff. The model includes the standard set of variables and economic logic that are necessary for the kinds of forecasting, economic policy, and budgetary planning analysis typically conducted by central ministries. In addition to standard outputs (unemployment, inflation, gross domestic product growth, and fiscal and current accounts), the model generates climate outcomes (tons of carbon emitted and economic and health damages due to higher temperatures and pollution). These outcomes are generated when specific climate policies such as mitigation are analyzed, but also when other policies are analyzed that might have unanticipated climate impacts. The paper describes the changes made to the World Bank’s standard macro structural model, MFMod, in integrated climate outcomes, climate policies, and the economic impacts of climate on Pakistan’s economy. Notably, carbon-tax scenarios show that a $20 carbon tax can reduce emissions in Pakistan by 36 percent by 2050. Gross domestic product impacts could also be positive, if the revenues from the carbon tax were used to reduce reliance on heavily distorting taxes. The model also quantifies associated co-benefits from reduced local air pollution and better health and productivity outcomes. In the absence of action to restrain climate change, the model suggests that increased temperatures and rain variability could reduce output by as much as 10 percent compared with a scenario where global temperature rises were minimized.